Tasha's cauldron of everything. (Dungeons & dragons., 2020)
The wizard Tasha has gathers bits and bobs of precious lore during her illustrious career as an adventurer. Her enemies wouldn't want these treasured secrets scattered across the multiverse, so in defiance she has collected and codified them for the enrichment of all! Baked into this book are rule options for all the characters classes in the Player's Handbook-- including new subclasses. And the book is sprinkled with the archmage's musings on everything from her wizardly rivals to the nature of the multiverse. -- adapted from back cover.